The role of base-rate neglect in cyberchondria and health anxiety - Nicolai, Jennifer; Moshagen, Morten; Schillings, Katharina; Erdfelder, Edgar (Journal of anxiety disorders, 2022)
Cyberchondria is characterized by excessive health-related online search behavior associated with an unfounded escalation of concerns about common symptomatology. It often co-occurs with health anxiety. We investigated whether base-rate neglect–the cognitive bias to ignore a priori probabilities (e.g., of serious diseases)–plays a significant role in cyberchondria and health anxiety. 368 participants were randomly assigned to eight experimental conditions, manipulating the base-rate (30 % vs. 70 %), the judgment domain (health-neutral versus health-related), and the salience of base-rate information (low vs. high) in a 2×2×2 between-subjects design when asking them for probability judgments with versus without disease relevance. We found that high salience decreased base-rate neglect in participants with low, but not in those with elevated levels of either cyberchondria or health anxiety. Under low salience conditions, however, both cyberchondria and health anxiety severity were uncorrelated with base-rate neglect. These effects were independent of whether health-related or health-neutral problems were evaluated. Our findings suggest a domain-general probabilistic reasoning style that may play a causal role in the pathogenesis of cyberchondria and health anxiety. •Investigated the role of base-rate neglect in cyberchondria and health-anxiety (HA).•No relation between base-rate neglect and cyberchondria/HA under low salience.•High salience decreased base-rate neglect in participants with low cyberchondria/HA.•Suggests a domain-general probabilistic reasoning style in cyberchondria and HA.